Magnetic cation exchange isolation of lysozyme from native hen egg white - Safarik, Ivo (Array, 2007)
Two magnetic macroporous cellulose cation exchangers (Iontosorb MG CM 100 and Iontosorb MG SHP 100) were used for one-step isolation of lysozyme from native, undiluted hen egg white. Highly purified lysozyme (purity >96 %) with specific activity similar to that of commercial lysozyme preparations was obtained in both cases. Carboxymethyl-based cation exchanger exhibited substantially higher capacity for lysozyme; maximum adsorption capacity was 138 mg/mL. The lysozyme-depleted egg white can be used in the same way as the routinely used egg white because no dilution of this material was necessary during the purification process